Lu–Hf garnet dating and the timing of collisions: Palaeoproterozoic accretionary tectonics revealed in the Southeastern Churchill Province, Trans‐Hudson Orogen, Canada. (18th March 2021) - Godet, Antoine; Guilmette, Carl; Labrousse, Loic; Smit, Matthijs A.; Cutts, Jamie A.; Davis, Donald W.; Vanier, Marc‐Antoine
Abstract: Dating the onset of continental collision is fundamental in defining orogenic cycles and their effects on regional tectonics and geodynamic processes through time. Part of the Palaeoproterozoic Trans‐Hudson Orogen, the Southeastern Churchill Province (SECP) is interpreted to result from the amalgamation of Archean to Palaeoproterozoic crustal blocks (amalgamated as the central Core Zone) that diachronically collided with the margins of the North Atlantic and Superior cratons, resulting in two bounding transpressive orogens: the Torngat and New Quebec Orogens. The SECP exposes mainly gneissic middle to lower orogenic crust in which deformation and amphibolite to granulite facies metamorphism and anatexis overprinted the early geological features classically used to constrain the timing of collisional events. To enable improved tectonic models for the development of the SECP, and the Trans‐Hudson as a whole, we investigated granulite facies supracrustal sequences from the Tasiuyak Complex (TC) accretionary prism and the western margin of the North Atlantic Craton—that is, Saglek Block (upper plate)—using a multi‐chronometer approach coupled with trace element geochemistry. In particular, the use of garnet Lu–Hf geochronology provides an important minimal time constraint for crustal thickening and collision. Garnet growth in the TC is constrained at 1885 ± 12 Ma (Lu–Hf), indistinguishable from U–Pb age of prograde monazite at 1873 ± 5 Ma. Zircon growth during melt crystallization occurred at 1848 ± 12 Ma. Garnet from the overriding Saglek Block is dated at 2567 ± 4.4 Ma (Lu–Hf) and indicates that gneissic rocks from the upper plate did not record the metamorphic imprint of the Torngat Orogeny. The diachronicity of the integrated metamorphic record across the strike of the SECP is explained by the location of terrane boundaries, consistent with the westward growth of the Churchill plate margin through sequential amalgamation of narrow crustal blocks during accretionary tectonics from c . 1.9 to 1.8 Ga.